Navigating Darkness: An analytical study of Psychological Challenges and Coping Mechanisms Among Adults with Visual Impairment - Amna Bakhtawar (South Eastern European Journal of Public Health, 2025)
This study investigates the psychological challenges and coping mechanisms of adults with visual impairment (VI), highlighting the psychosocial dimensions of their lived experiences. Visual impairment affects over 2.2 billion people worldwide which significantly impact emotional wellbeing, social interactions and daily functioning. Using a mixed methods approach with 100 participants aged 18–65 the study combines quantitative surveys (e.g., PHQ-9, GAD-7) and qualitative interviews to explore issues such as depression, anxiety and social isolation. Key findings show that 58% experience depressive symptoms while 65% report anxiety and social isolation is prevalent. Effective coping strategies include problem focused approaches like assistive technologies and skill building which is supported by strong social networks. Barriers such as socioeconomic status and limited access to resources worsen challenges for low income individuals. Thestudy advocates for integrating mental health services into rehabilitation with inclusive workplace policies and community based interventions while emphasizing the importance of addressing societal barriers to improve the wellbeing and social inclusion of individuals with VI..IntroductionVisual impairment (VI) refers to a range of conditions in which an individual's visual function cannot be fully corrected through conventional lenses or medical interventions (WHO, 2021). Affecting at least 2.2 billion people worldwide, VI is a significant public health concern, particularly in low-andmiddle-income countries where access to eye care remains limited (Pascolini & Mariotti, 2012). While many cases are preventable or treatable, socioeconomic constraints and inadequate healthcare infrastructure contribute to high prevalence rates. Beyond physical limitations VI profoundly impacts daily functioning, social engagement, and mental health, making routine activities such as reading, navigation and recreation more challenging (Chang & Nickerson, 2018; Papadopoulos, Montgomery, & Chronopoulou, 2014). Increased dependency on others can lead to social isolation, lower self-esteem and emotional distress (Cimarolli & Boerner, 2005).Despite extensive research on the medical and rehabilitative aspects of VI (Corn & Lusk, 2018), fewer studies have explored the psychosocial challenges adults with VI face in their daily lives (Chang & Nickerson, 2018). These challenges including mental health concerns and social stigmarequire deeper examination to understand how individuals manage and cope with them. Since effective coping strategies can significantly enhance well-being and social